Randomized clinical trial in cancer patients shows immune metabolic effects exerted by formulated bioactive phenolic diterpenes with potential clinical benefits - Gómez de Cedrón, Marta; Moreno-Rubio, Juan; de la O Pascual, Victor; Alvarez, Beatriz; Villarino, Marta; Sereno, María; Gómez-Raposo, César; Roa, Silvia; López Gómez, Miriam; Merino-Salvador, María; Jiménez-Gordo, Ana; Falagán, Sandra; et al. (Frontiers in Immunology, 2025)
BackgroundNutrients, including bioactive natural compounds, have been demonstrated to affect key metabolic processes implicated in tumor growth and progression, both in preclinical and clinical trials. Although the application of precision nutrition as a complementary approach to improve cancer treatments is still incipient in clinical practice, the development of powerful “omics” techniques has opened new possibilities for delivering nutritional advice to cancer patients. Precision nutrition may contribute to improving the plasticity and function of antitumor immune responses.ObjectivesHerein, we present the results of a randomized, prospective, longitudinal, double-blind, and parallel clinical trial (NCT05080920) in cancer patients to explore the immune-metabolic effects of a bioactive formula based on diterpenic phenols from rosemary, formulated with bioactive alkylglycerols (Lipchronic© WO/2017/187000). The trial involved cancer patients, including those with lung cancer (LC), colorectal cancer (CRC), and breast cancer (BC), undergoing chemotherapy, targeted biological therapy, and/or immunotherapy. The main readouts of the study were the analysis of Lip on systemic inflammation, hemogram profile, anthropometry, lipid and glucose profiles, and tolerability. Additionally, a deep immune phenotyping of peripheral blood mononuclear cells (PBMCs) was performed to identify the functional effects of Lip on key mediators of the immune system.ResultsLip was well tolerated. The lung cancer subgroup of patients showed a reduction in biomarkers of systemic inflammation, including the neutrophil-to-lymphocyte ratio (NLR). Furthermore, modulation of key players in the immune system associated with the experimental treatment Lip compared to the control placebo (Pla) treatment was revealed, with particularities among the distinct subgroups of patients. Our results encourage further research to apply molecular nutrition-based strategies as a complementary tool in the clinical management of cancer patients, particularly in the current era of novel immunotherapies.Clinical trial registrationClinicalTrials.gov, identifier NCT05080920